Establishment of Infection Models in Zebrafish Larvae (Danio rerio) to Study the Pathogenesis of Aeromonas hydrophila - Saraceni, Paolo R.; Romero, Alejandro; Figueras, Antonio; Novoa, Beatriz (Frontiers in Microbiology, 2016)
Aeromonas hydrophila is a Gram-negative opportunistic pathogen of fish and terrestrial animals. In humans, A. hydrophila mainly causes gastroenteritis, septicaemia and tissue infections. The mechanisms of infection, the main virulence factors and the host immune response triggered by A. hydrophila have been studied in detail using murine models and adult fish. However, the great limitation of studying adult animals is that the animal must be sacrificed and its tissues/organs extracted, which prevents the study of the infectious processes in the whole living animal. Zebrafish larvae are being used for the analysis of several infectious diseases, but their use for studying the pathogenesis of A. hydrophila has never been explored. The great advantage of zebrafish larvae is their transparency during the first week after fertilization, which allows detailed descriptions of the infectious processes using in vivo imaging techniques such as differential interferential contrast (DIC) and fluorescence microscopy. Moreover, the availability of fluorescent pathogens and transgenic reporter zebrafish lines expressing fluorescent immune cells, immune marker genes or cytokines/chemokines allows the host-pathogen interactions to be characterized. The present study explores the suitability of zebrafish larvae to study the pathogenesis of A. hydrophila and the interaction mechanisms between the bacterium and the innate immune responses through an infection model using different routes for infection. We used an early-embryo infection model at 3 days post-fertilization (dpf) through the microinjection of A. hydrophila into the duct of Cuvier, caudal vein, notochord or muscle and two bath infection models using 4 dpf healthy and injured larvae. The latter resembled the natural conditions under which A. hydrophila produces infectious diseases in animals. We compared the cellular processes after infection in each anatomical site by confocal fluorescence imaging and determined the implication of inflammatory immune genes by measuring gene expression by qPCR.